Application of a new nanoporous sorbent for extraction and pre-concentration of lead and copper ions. Issue 4 (16th March 2017) - Zarezade, Vahid; Aliakbari, Azam; Es'haghi, Moosa; Amini, Mostafa M.; Behbahani, Mohammad; Omidi, Fariborz; Hesam, Ghasem
ABSTRACT: The authors describe a method for the trace determination of copper (II) and lead (II) in water and fish samples using solid-phase extraction via siliceous mesocellular foam functionalised by dithizone. Siliceous mesocellular was functionalised with dithizone, and the resulting sorbent was characterised by scanning electron microscopy, surface area analysis, thermogravimetric/differential thermal analysis and FTIR. Following solid-phase extraction of target ions by the sorbent, copper and lead ions were quantified by flame atomic absorption spectrometry. Factors affecting the sorption and desorption of target ions by the sorbent were evaluated and optimised. The calibration plot is linear in the 1 – 500 μg L −1 copper (II) and 3–700 μg L −1 lead (II) concentration range. The relative recovery efficiency in real sample analysis is in the range from 96 to 102%, and precision varies between 1.7 and 2.8%. It is should be noted that the limits of detection for the copper and lead analysis were 0.8 and 1.6 μg L −1, respectively. Also, the adsorption capacities for copper and lead ions were 120 and 160 mg g −1, respectively. The obtained pre-concentration factor for the lead and copper ions by the proposed solid-phase extraction was 75. The method was successfully applied to the determination of low levels of copper (II) and lead (II) in tap, Caspian sea, Persian gulf and lake water and also their detection in fish samples.